2007
DOI: 10.1055/s-2007-965008
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Blunt Abdominal Trauma: Challenges of Management in a Developing Country

Abstract: Blunt abdominal trauma in children resulted mainly from road traffic accidents. The use of a simple protocol supported by ultrasound scan could reduce the laparotomy rate in countries with limited facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
4
18
2
Order By: Relevance
“…It also occurred more in males which is in tandem with patterns documented in literature 25,26 . Although the liver and spleen were the most injured intra-abdominal organs in blunt abdominal trauma [25][26][27] , there was a slightly higher incidence of traumatic gut perforation in our study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It also occurred more in males which is in tandem with patterns documented in literature 25,26 . Although the liver and spleen were the most injured intra-abdominal organs in blunt abdominal trauma [25][26][27] , there was a slightly higher incidence of traumatic gut perforation in our study.…”
Section: Discussionsupporting
confidence: 86%
“…It also occurred more in males which is in tandem with patterns documented in literature 25,26 . Although the liver and spleen were the most injured intra-abdominal organs in blunt abdominal trauma [25][26][27] , there was a slightly higher incidence of traumatic gut perforation in our study. Nigeria by Ameh et al and Chirdan et al 18,25,26 had shown that a sizeable proportion of children with blunt abdominal injuries can be managed non-operatively.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The organ most often injured was the spleen, similar to reports from Nigeria. [18] As a result, many spleens were removed for various grades of splenic injuries. Since 2003, we have reviewed our stand on exploratory laparotomies for all cases of hemoperitoneum involving the spleen, taking into consideration the immunologic role of the spleen and the improvement of the diagnostic tools for blunt abdominal trauma in our hospital, and have evolved nonoperative methods of management of most splenic injuries, as accepted in many centers worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…[2,[9][10][11][12][13][14][15][16][17][18][19][20] In developing countries, such as Nigeria, however, lack of imaging facilities or inability to afford them even when available make it a great challenge to embark on non operative management. [1,[20][21][22][23][24][25] In view of this, laparotomy with splenorrhaphy or splenectomy continued to remain the standard treatment in this centre. [20] Splenorrhaphy in children who reside in regions where malaria is endemic is very difficult as the splenic capsule is attenuated and holds sutures poorly.…”
Section: Introductionmentioning
confidence: 99%